Risk-based availability modelling and reputation management on fault tolerant cloud computing systems. (2019) - Mani, Deepa; Mahendran, Anand
This paper exhibits a risk-based philosophy in cloud computing to estimate ideal quality and maintenance which maximise the high availability of cloud administration infrastructure. The procedure is confined into two stages: 1) accessibility displaying the cloud; 2) hazard based assessment. The projected procedure is practical to the healthcare scheme using Markov chain process. The proposed system predicts, mitigate and eliminate the risk-based inspection and Markov chain process to efficiently identify the repair and failures of each virtual machine and reduce the energy consumption rate. The result of our proposed method will definitely bound optimum solutions and specifies the conquest of an efficient risk-based availability modelling on minimal cost and energy consumption. Finally, the proposed model is verified by the Nagios and OPTIMIS toolkit. The result obtained in our proposed model definitely bounds optimum solutions and triumph of an efficient risk analysis of failures on minimal cost and energy consumption.